Aplicación de una auditoría de gestión en la cámara de comercio de la ciudad de Latacunga, provincia de Cotopaxi, comprendido entre el período 1 de enero al 31 de diciembre del 2014 - Tapia Zapata, Daniela Estefanía (2016)
This Project was performed given that the Chamber of Commerce of Latacunga, presented inconformity between the business associate, provoking their massive disaffiliation, that is why we saw the need to apply a Management Audit, between the period January 1st to December 31st, 2014 through the use of management indicators that permit to measure the level of efficiency, efficacy and effectiveness, economy, equity and ecology in the institution, for the evaluation of the company we were used techniques such as interview and surveys, applied to the president and employees respectively permitting with this gather the necessary information . To apply the propose, it was determined that the institution reached efficiency, efficacy and economy….